The stock-take - Pryor, Geoff, 1944- (1992)
With Russian soldiers under attack in the Transcaucuses in Nagorno-Karabakh and Ukraine threatening to suspend the transfer of tactical nuclear weapons back to Russia, the Commonwealth of Independent States (comprised of the republics of the former Soviet Union) is off to a shaky start since its creation in the previous December. Perhaps it would be useful to know who has what and where.--Information provided by Geoff Pryor.
Published in the Canberra Times on 16 March 1992.
Part of the Pryor collection of cartoons and drawings.
Also available online
Keywords: Disarmament -- Soviet Union -- Caricatures and cartoons; Soviet Union -- Politics and government -- 1953-1985 -- Caricatures and cartoons